META-ANALISIS PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK SMA - Selvi Seftiani; Zulyusri Zulyusri; Fitri Arsih; Lufri Lufri (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2021)
This research aims to analyze the effect of Project Based Learning on students' critical thinking abilities. The method of this study is a meta-analysis with a sample of 10 journals of education and research theses in national journals and instruments in the form of coding categories. The meta-analysis study shows that the effect of Project Based Learning on students' critical thinking abilities from the subject level of education, Project Based Learning is equally positive for both high school (SMA) and vocational levels (SMK) but is more effectively used by students in high school education. Meanwhile from subject matter subjects, Project Based Learning is more influential digestion material than other material. And from the subject of Media that is used, Project Based Learning has a positive effect when using real or virtual media. Other findings show that Project Based Learning has a high influence on students' critical thinking skills.